7075-T6 aluminium alloy exfoliation corrosion sensitivity and electrochemical impedance spectroscopy under stress. (December 2015) - Ji, Z. H.; Jing, Z. Z.
Abstract : Exfoliation corrosion susceptibility under tensile-bending stress of 7075-T6 aluminium alloy was tested with a self-made tri-fulcrums loading fixture. The test results of both microscopic characterisation and electrochemical impedance spectroscopy indicate that the alloy's exfoliation corrosion susceptibility in exfoliation corrosion solution increases evidently for tensile-bending stress. The electrochemical impedance spectroscopy of the loaded sample soaked for 12 hours manifests double capacitance arcs as the mark of propagated exfoliation corrosion, which takes 24 hours for the unloaded one to reach the same results. Results analysed by equivalent circuit model also prove the accelerating effect of tensile-bending stress on exfoliation corrosion susceptibility.